Enhancement through sensitization of VUV-excited luminescence in red-emitting pentaborate phosphors - Mikhailik, V; Kraus, H (2010)
We studied the feasibility of using sensitization for the improvement of the VUV-to-visible conversion efficiency of red-emitting pentaborate phosphor. It is shown that Tb 3+ ions that exhibit a strong absorption throughout the 160-230 nm wavelength range facilitate enhancement of Eu3 emission in TbM gB 5O 10-Eu at excitation in this spectral range. The maximum increase of the Eu 3+ emission efficiency in a pentaborate host at excitation with 150 nm photons is ca.10%. It is also shown that substitution of Zn for Mg in Gd(Mg,Zn)B 5O 10- Mn phosphor results in strong (up to 2.4 times) enhancement of the intensity of Mn 2+ emission. A possible reason for the observed host sensitization effect is discussed. © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.